Modelling Australian Public Service Careers - Robert Breunig; David Hansell; Nu Nu Win (Institute of Labor Economics (IZA), 2023)
We investigate whether being female, from a non-English speaking background (NESB) or having a disability affects career advancement in the Australian Public Service. Over the past twenty years, women have become more likely to get promoted at senior ranks than similar men and just as likely at junior ranks. Disability lowers promotion prospects at most ranks. NESB staff have much lower promotion prospects at higher ranks despite being less likely to separate from the public service. These lower promotion prospects for NESB staff are only partially explained by language proficiency or cultural assimilation. The unexplained remainder could reflect a penalty for having non-European features.
Keywords: J15; J18; J45; J78; 330; public sector employment; affirmative action policies; equal opportunity employment